2012
DOI: 10.1186/2046-2530-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Tubby is required for trafficking G protein-coupled receptors to neuronal cilia

Abstract: BackgroundTubby is the founding member of the tubby-like family of proteins. The naturally occurring tubby mutation in mice causes retinitis pigmentosa, hearing loss and obesity. Tubby has been proposed to function as an accessory factor in ciliary trafficking. We directly examined a role for tubby in ciliary trafficking in vivo.MethodsWe used immunofluoresence labeling to examine the subcellular localization of rhodopsin, somatostatin receptor 3 (SSTR3) and melanin concentrating hormone receptor 1 (MCHR1), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 66 publications
2
56
0
Order By: Relevance
“…TXNDC15 encodes a putative protein disulfide isomerase that contains a thioredoxin domain. Proteomic studies showed that TXNDC15 interacted with a total of 224 endomembrane-associated proteins after filtering (Additional file 5: Table S4) that were significantly enriched in known or predicted ciliary proteins (SYSCILIA Gold Standard, SCGSv1 [16]; p  = 2.34 × 10 -18 hypergeometric test, observed 39, expected 7.02). Furthermore, loss of TXNDC15 prevented correct localization of the TMEM67 ciliary receptor to the transition zone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TXNDC15 encodes a putative protein disulfide isomerase that contains a thioredoxin domain. Proteomic studies showed that TXNDC15 interacted with a total of 224 endomembrane-associated proteins after filtering (Additional file 5: Table S4) that were significantly enriched in known or predicted ciliary proteins (SYSCILIA Gold Standard, SCGSv1 [16]; p  = 2.34 × 10 -18 hypergeometric test, observed 39, expected 7.02). Furthermore, loss of TXNDC15 prevented correct localization of the TMEM67 ciliary receptor to the transition zone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Arl6/Bbs3 small GTPase is required for ciliary entry of the BBSome itself [28], whereas Ift25/Ift27 has been suggested to mediate ciliary exit of the BBSome-cargo complex [29,30]. Another family of proteins, the Tubby family, is also critical for ciliary localization of a subset of GPCRs [31,32]. The tubby mouse has spontaneous maturity-onset obesity as well as retinal and olfactory degeneration [33,34] and the Tulp3 knockout mouse is embryonic lethal due to aberrant hedgehog signaling [35,36].…”
Section: Ciliary Gpcr Signalingmentioning
confidence: 99%
“…More recently, an alternate hypothesis has been proposed that the mislocalization of other GPCRs to the cilium may be responsible for hyperphagia-induced obesity in BBS (Loktev and Jackson, 2013). A screen for novel ciliary GPCRs led to the identification of neuropeptide Y receptor NPY2R as a candidate anorexigenic receptor defective in hypothalamic signaling in BBS and tubby (a ciliary protein required for the trafficking of GPCRs to neuronal cilia; mouse mutants show retinal degeneration and obesity phenotypes (Mukhopadhyay et al, 2010; Sun et al, 2012)) mutant mice. Importantly, mutant BBS mice were non-responsive to treatment with PYY3-36, an endogenous ligand to NPY2R, suggesting that ciliary targeting of additional GPCRs (Figure 1) may either drive or modulate the obesity phenotypes observed in ciliopathies (Loktev and Jackson, 2013).…”
Section: Introductionmentioning
confidence: 99%